Correlation between flexibility and muscular power in vertical jumps in women practitioners handball and weight lifters - Igor Martins Barbosa; Hyago Bernardes da Rosa; Lucas Souza Santos; Samuel Klippel Prusch; Vinicius da Silva Lessa de Oliveira; Luiz Fernando Cuozzo Lemos (Universidade Estadual de Maringá, 2018)
The present study has the objective to correlate the variables of flexibility and muscle power present in the vertical jumps, through tests done with female individuals, performing analyzes about two groups: Handball players (HG); weight lifters (WL). Initially, the protocol consisted on the performing of the flexibility test at Wells Bank. Subsequently, the jump test was performed, using the Counter movement jump (CMJ) and Squat jump (SJ). About the study groups, it can be observed that they have similar physical characteristics, but practice times (HG = 9.25 ± 3.28  versus WL = 1.85 ± 1.47 years) and weekly hours of activities (HG = 3.33 ± 1.23 versus WL = 5.29 ± 1.81 hours) were distinct. In the execution of SJ for HG, a high correlation was presented for all variables (Height 0.615; Power 0.718; Standard power 0.618). It also presented a high correlation in the non-normalized power (0.688) in CMJ. WL did not present a significant correlation for any of the variables. Based on the findings of the present study, jump test results have correlation with variables of flexibility, muscle power and handball players. However, there is no correlation for any variable for weight lifters.